Midkine Is a Novel Regulator of Amphetamine-Induced Striatal Gliosis and Cognitive Impairment: Evidence for a Stimulus-Dependent Regulation of Neuroinflammation by Midkine - Marta Vicente-Rodríguez; Rosalía Fernández-Calle; Esther Gramage; Carmen Pérez-García; María P. Ramos; Gonzalo Herradón (Hindawi Limited, 2016)
Midkine (MK) is a cytokine that modulates amphetamine-induced striatal astrogliosis, suggesting a possible role of MK in neuroinflammation induced by amphetamine. To test this hypothesis, we studied astrogliosis and microglial response induced by amphetamine (10 mg/kg i.p. four times, every 2 h) in different brain areas of MK−/− mice and wild type (WT) mice. We found that amphetamine-induced microgliosis and astrocytosis are enhanced in the striatum of MK−/− mice in a region-specific manner. Surprisingly, LPS-induced astrogliosis in the striatum was blocked in MK−/− mice. Since striatal neuroinflammation induced by amphetamine-type stimulants correlates with the cognitive deficits induced by these drugs, we also tested the long-term effects of periadolescent amphetamine treatment (3 mg/kg i.p. daily for 10 days) in a memory task in MK−/− and WT mice. Significant deficits in the Y-maze test were only observed in amphetamine-pretreated MK−/− mice. The data demonstrate for the first time that MK is a novel modulator of neuroinflammation depending on the inflammatory stimulus and the brain area considered. The data indicate that MK limits amphetamine-induced striatal neuroinflammation. In addition, our data demonstrate that periadolescent amphetamine treatment in mice results in transient disruption of learning and memory processes in absence of endogenous MK.